Analisis Pengaruh Modal Sendiri dan Modal Pinjaman Terhadap Sisa Hasil Usaha Pada Koperasi Simpan Pinjam dan Pembiayaan Syariah di Bmt Ugt Sidogiri Capem Gumukmas Tahun 2018-2020 - Susila, Ahdiyat Agus; Rahman, Moh. Abd. (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2023)
The purpose of this study was to determine: (1) The effect of own capital on the remaining results of operations in savings and loan cooperatives and Islamic financing at BMT UGT Sidogiri Capem Gumukmas in 2018-2020 (2) The effect of loan capital on the remaining results of operations in savings and loan cooperatives and Islamic financing at BMT UGT Sidogiri Capem Gumukmas in 2018-2020 (3) The effect of own capital and loan capital on the remaining results of operations in savings and loan cooperatives and Islamic financing at BMT UGT Sidogiri Capem Gumukmas in 2018-2020. The techniques in the research data collection method used are documentation and interviews. While the technique in data analysis used through multiple linear regression analysis with t test and F test. The results of this study indicate that; (1) Own capital has a significant effect on the acquisition of SHU with tcount > ttable (4.959 > 2.042) with a significance level of 0.000 < 0.05. (2) Loan capital has no effect on the remaining results of operations with tcount > ttable (-1.526 < 2.042) and with a significance of 0.138 > 0.05.